HUBUNGAN FAKTOR PENGETAHUAN TENTANG ALAT PELINDUNG DIRI (APD) DENGAN PERILAKU KEPATUHAN PENGGUNA ALAT PELINDUNG DIRI (APD) PEKERJA PEST KONTROL DI KABUPATEN TANGERANG - Rita Haerani; Deni Kurniawan (FT-USNI, 2021)
This study aims to determine the relationship between knowledge of personal protective equipment and employee compliance in the use of personal protective equipment. The method used is descriptive quantitative. Analysis of the data used is correlation regression. Respondents in this study were workers at Pest Control in Tangerang. The results show that there is a significant relationship between knowledge of personal protective equipment and employee compliance in using personal protective equipment